Determination of sulphur in various vegetables by solid sampling high-resolution electrothermal molecular absorption spectrometry - Gunduz, Sema; Akman, Suleyman (Elsevier BV, 2015)
Sulphur was determined in various vegetables via molecular absorption of carbon monosulphide (CS) at 258.056 nm using a solid sampling high resolution continuum source electrothermal atomic absorption spectrometer (SS HR-CS ETAAS). Samples were dried, ground and directly introduced into the ruthenium coated graphite furnace as 0.05 to 0.50mg. All determinations were performed using palladium+citric acid modifier and applying a pyrolysis temperature of 1000 °C and a volatilisation temperature of 2400 °C. The results were in good agreement with certified sulphur concentrations of various vegetal CRM samples applying linear calibration technique prepared from thioacetamide. The limit of detection and characteristic mass of the method were 7.5 and 8.7 ng of S, respectively. The concentrations of S in various spinach, leek, lettuce, radish, Brussels sprouts, zucchini and chard samples were determined. It was showed that distribution of sulphur in CRM and grinded food samples were homogeneous even in micro-scale.
Keywords: Spectrophotometry, Atomic; Calibration; Vegetables; Temperature; Sulfur